Peran Dinas Pendidikan Dalam Wajib Belajar di Tinjau Menurut Fiqh Siyasah - Alawiyah, Rafida (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research discusses the Role of the Education Office in the Compulsory Education Program in the New Village of Batahan District, West Pasaman Regency, this research was motivated by the large number of children who Drop out of school and prefer to work while judging from the age of children aged 7-18 years should be eligible to sit in the pendidiment and complete their education until produce diplomas from elementary, junior high and high school so as to cause implementation that is not in accordance with existing rules. This type of research is field research (Field Researche) using qualitative descriptive analysis methods, this method of collecting data collection is by interview and documentation. The parties studied are the West Pasaman Regency Education Office, The Community and Children who dropped out of school in the NewVillage of West Pasaman Regency. The results of the study that said that the Role of the Education Officeinthe Compulsory Education Program in the NewVillage of Batahan District of West Pasaman Regencyhave been carried out. This is seen from the form of implementation that has been implemented by the Education Office by socializing to schools, UPTD and the community, but not yet maximal and still Many children drop out of school and prefer to work and do not produce a diploma.